Improving mechanical properties and shrinkage cracking characteristics of soft clay in deep soil mixing - Chompoorat, Thanakorn; Thepumong, Thanakit; Khamplod, Anupong; Likitlersuang, Suched (Construction & building materials, 2022)
•Suitable soft clay stabilised with OPC and FA for deep soil mixing is assessed.•FA can be applied as a shrinkage-reducing agent for cement stabilised soft clay.•Inclusion of 15% FA with B/wc of 0.4 satisfies strength and shrinkage requirements.•Correlations between mechanical properties and chemical compositions are proposed. Deep soil mixing is a ground improvement method that enhances the characteristics of soft soils by mechanically mixing the soil with cementitious binders such as cement and fly ash (FA). The objective of this paper is to investigation the post-treatment mechanical properties and shrinkage cracking characteristics of soft Bangkok clays treated with ordinary Portland cement (OPC) and FA. Unconfined compressive strength, modulus of elasticity, and shrinkage cracking after 7 and 28 days of mixture curing were measured. The effects of wet/dry cycling on the durability of mixtures were examined. Microstructures of treated soft clays were examined using scanning electron microscopy with energy dispersive x-ray analysis (SEM/EDX) techniques. Test results showed that strength and stiffness improvements of stabilised soft clays increased with OPC content but decreased with FA content, while the extent of sample shrinkage decreased with increasing FA content. Based on these results, we propose the preliminary guideline of applying 15% replacement of OPC with FA to obtain the optimal mixture ratios that allows FA to act as a shrinkage-reducing agent for deep soil mixing purposes. By adding OPC and 15% FA at a binder-per-water ratio (B/wc) of 0.4, the stabilised soft clay satisfied both strength and shrinkage cracking criteria for deep soil mixing purposes. SEM/EDX analyses further supported these experiment results. In addition, correlations between the mechanical properties and the chemical compositions of stabilised soft clay were derived and presented.